Cationic Emulsion-Based Artificial Tears as a Mimic of Functional Healthy Tear Film for Restoration of Ocular Surface Homeostasis in Dry Eye Disease - Daull, Philippe; Amrane, Mourad; Ismail, Dahlia; Georgiev, Georgi; Cwiklik, Lukasz; Baudouin, Christophe; Leonardi, Andrea; Garhofer, Gerhard; Garrigue, Jean-Sebastien (Journal of ocular pharmacology and therapeutics, 2020)
Dry eye disease (DED) is a complex multifactorial disease that affects an increasing number of patients worldwide. Close to 30% of the population has experienced dry eye (DE) symptoms and presented with some signs of the disease during their lifetime. The significant heterogeneity in the medical background of patients with DEs and in their sensitivity to symptoms renders a clear understanding of DED complicated. It has become evident over the past few years that DED results from an impairment of the ocular surface homeostasis. Hence, a holistic treatment approach that concomitantly addresses the different mechanisms that result in the destabilization of the tear film (TF) and the ocular surface would be appropriate. The goal of the present review is to compile the different types of scientific evidence (from in silico modeling to clinical trials) that help explain the mechanism of action of cationic emulsion (CE)-based eye drop technology for the treatment of both the signs and the symptoms of DED. These CE-based artificial tear (AT) eye drops designed to mimic, from a functional point of view, a healthy TF contribute to the restoration of a healthy ocular surface environment and TF that leads to a better management of DE patients. The CE-based AT eye drops help restore the ocular surface homeostasis in patients who have unstable TF or no tears.
Keywords: homeostáza; Emulsions; Ocular Physiological Phenomena; povrchové vlastnosti; Lubricant Eye Drops; Homeostasis; Adult; dospělí; artificial tear; emulze; Dry Eye Syndromes; cationic emulsion; tear film lipid layer; syndromy suchého oka; lidé; zvlhčující oční kapky; Humans; polar lipid; Surface Properties; oči - fyziologické jevy; Tears; zdraví dobrovolníci pro lékařské studie; dry eye; slzy; Healthy Volunteers